Combining performance based lab tests and finite element modeling to predict life-time of bituminous bound pavements. (1st August 2015) - Hofko, Bernhard
Highlights: Combining data from stress in motion and 4-PBB tests with finite element simulation. Using data of dynamic measurements from actual tires instead of static data. Comparing impact of super-single and twin tires on fatigue of European pavements. Super-single tires mean higher stresses for pavements and thus shorter life-times. The influence of the tire pressure is stronger for super-single tires. Abstract: As roads are subjected to high traffic loads due to the strong growth in heavy vehicle traffic and new trends in the automotive and tire industries, the traditional asphalt mix tests are often inadequate for a reliable prediction of the in-service performance of flexible road pavements. With performance-based test methods (PBT) at hand, the thermo-rheological properties of hot mix asphalt can be obtained. This paper presents results of a research project where 4-point bending beam (4-PBB)-tests are carried out on different AC mixes for base layers at various temperatures and frequencies to obtain stiffness and fatigue behavior. At the same time, linear elastic finite element simulations are performed with input data for the materials different from the 4-PBB. These simulations are carried out on two different pavement structures, different tire types (twin-tires and wide base super-single tires) and wheel configurations (tire load and pressure). Loading data for the tires are obtained from stress-in-motion measurements using the Vehicle–Road Surface Pressure Transducer Array (VRSPTA). The strain at the bottom of the bituminous bound layers are taken from the simulations and used in combination with the fatigue functions to evaluate the life-time in permissible load cycles for different tire configurations. The main findings are that super-single tires lead to significantly lower pavement life-times than the standard twin-tire configuration and that the relative difference increases with decreasing thickness of the pavement structure. Also, the tire pressure has a strong impact on the pavement life-time; an increase in tire pressure by 60% decreases the life-time by 25–52% (super-single) and 15–38% (twin-tire) respectively.